The Correlation Between Learning Styles and Student Learning Outcomes in Social Studies: Korelasi Antara Gaya Belajar dan Hasil Belajar Siswa dalam Mata Pelajaran IPS - Dwiyul Tiara, Vira; Tetep; Mulyana, Eldi (Institut Pendidikan Indonesia, 2022)
Learning styles can be classified into three types, namely visual learning styles, auditory learning styles and kinesthetic learning styles. Each individual has a tendency to a certain learning style that makes it easier for him to absorb lessons. Individuals who know their learning style tendencies and are able to apply appropriate learning strategies will be successful in their studies. The purpose of this study is to determine the relationship between learning styles and learning outcomes for class VIII students in social studies subjects at SMPN 01 Cisompet. The research approach uses quantitative with the type of correlation research. The sample in this study amounted to 31 respondents. Data collection was obtained through questionnaires and documentation. After the data is collected in hypothesis testing, the product moment correlation test and the coefficient of determination test are used which are processed with the help of SPSS 16 for Windows and Microsoft Excel. The results of the study describe that there is a significant relationship between learning styles and social studies learning outcomes for class VIII at SMPN 01 Cisompet. The magnitude of the relationship between the two variables is 0.993 where the value is in the very high category. The magnitude of the contribution of the influence of learning styles on student learning outcomes is around 98.5%.